Assessment Purposes, Practices, and Discourses: Learnings from a Conceptual Review of Literature - Arshad, Muhammad Adil; Kenny, Natasha; Brown, Barbara (Imagining SoTL)

(untitled) (Mount Royal University Library in partnership with University of Alberta Library, 2026)
There is an increased focus on the assessment of student learning, particularly as postsecondary institutions are orienting towards principle-based assessment policies and practices. We conducted a conceptual review of the literature to identify the purposes, practices, and discourses surrounding the assessment of student learning. The review of 34 publications offers valuable insights into the assessment landscape, emphasizing the shift towards approaches such as the assessment for learning, assessment as learning and empowerment, and learning-oriented assessments. A few emergent themes included authentic assessment practices, engaging students as partners in assessment, online and digital assessment strategies, strengthening feedback pathways, supporting student and educator mental health and well-being, academic integrity, generative artificial intelligence, and ethical, inclusive, and equitable assessment. We invite instructors and educational leaders to consider contemporary purposes, practices, and discourses for the assessment of student learning and explore ways to enhance assessment processes and practices in their respective institutional contexts.